Systematic Literature Review: The Role of Insurance The journey of Sharia in Increase Protection Muslim Tourists - Marshanda Ridia Amelia; Taufiqur Rahman (Universitas Islam Negeri (UIN) Walisongo Semarang, 2025)
Purpose - This article aims to examine and analyze the role of Islamic travel insurance in improving protection for Muslim tourists. Specifically, this study focuses on understanding the mechanism of Islamic insurance, as well as the extent to which this insurance is able to answer the needs and challenges of Muslim travelers in the context of halal travel.. Method - In this study, data search was conducted using the Systematic Literature Review (SLR) Method by summarizing findings from previous studies that are relevant to the research topic. The keywords from Indonesian used to search for data for this study are